2012
DOI: 10.1016/j.neubiorev.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal meta-analysis of structural and functional brain changes in first episode psychosis and the effects of antipsychotic medication

Abstract: Structure and function in the human brain are closely related. At the onset of psychosis, brain imaging studies have identified robust changes in brain function and structure, but no data are available relating these two domains. After systematic literature searches, we included all available studies reporting whole-brain structural or cognitive functional imaging findings in first-episode (FEP) subjects in multimodal Signed Differential Mapping (SDM). Forty-three studies met the inclusion criteria. The struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
238
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(253 citation statements)
references
References 51 publications
13
238
1
1
Order By: Relevance
“…Given the association with schizophrenia, we focused our attention on regions defined by a recent meta-analysis of first-episode psychosis 21 (Fig. 3a).…”
Section: Structural Mri Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the association with schizophrenia, we focused our attention on regions defined by a recent meta-analysis of first-episode psychosis 21 (Fig. 3a).…”
Section: Structural Mri Phenotypesmentioning
confidence: 99%
“…Additional region-of-interest (ROI) analyses were performed in the following regions found to show both functional and structural abnormalities in a recent meta-analysis of subjects with high risk of schizophrenia 21 : anterior cingulate and medial frontal cortex, and bilateral insula extending into temporal and parietal cortex. Results of these ROI analysis were considered significant at P , 0.05 voxel level, FWE-corrected.…”
Section: Article Researchmentioning
confidence: 99%
“…In two recent meta-analyses of voxel-based volumetric studies in FEP, STG and insular volume loss were identified (Fusar-Poli et al, 2011b;Radua et al, 2012). Others identified right (Witthaus et al, 2009) and bilateral (Takahashi et al, 2010) STG reduction in individuals at ultra-high risk of psychosis (UHR), and a recent meta-analysis associated STG volume reduction with transition from UHR to psychosis (Fusar-Poli et al, 2011a).…”
Section: Cerebral Cortexmentioning
confidence: 99%
“…To examine the effects of age on GMV abnormalities in BPD, a meta-regression was conducted using a more conservative voxel-level threshold of p ≤ 0.0005 (uncorrected) in accordance with previous meta-analyses (Hart et al, 2012;Radua et al, 2012a;Lim et al, 2014). In line with this conservative approach, we decided to use a cluster-level extent threshold of k ≥ 20.…”
Section: Study Criteria and Data Extractionmentioning
confidence: 99%